Determining Factors for the Adoption of Islamic Insurance (Takaful) Business among Vehicle Owners in Nigeria - Sayedi, Shuaib Ndagi; Abdulkadir, Usman; Bagudu, Suleiman Ndako; Hassan, Abubakar (Universitas Ahmad Dahlan, 2023)
Introduction to The Problem: Despite the increase in growth rate and the influence Islamic financial system play in global financial system in recent decades, insurance (Takaful) as one of the three components of Islamic financial system has received little attention in Nigeria. Purpose/Objective Study: The study determined factors that influence vehicle owners’ intention to adopt auto – insurance in Nigeria. Design/Methodology/Approach: The study adopted survey research designs. The population of the study was 12,000,000 registered vehicles in Nigeria which 300 respondents were sampled. Questionnaire was the instrument for data collection. Findings: Regression result showed that awareness, relative advantage and social influence has significant influence on vehicle owners’ intention to adopt auto – insurance in Nigeria. But, religiosity, perceived compatibility, perceived complexity and perceived risk have no significant influence on vehicle owners’ intention to adopt auto – insurance in Nigeria.